Data Encryption Standard Algorithm in Multimodal Biometric Image - More, Sharmila S; Narain, Bhawna; Jadhav, B.T (International Journal of Computer Sciences and Engineering, 2025)
In every field of technology there are major issues of security. Biometric images are used as input and then the features like edge, texture are extracted. This is done by applying feature extraction algorithms and data encryption standard cryptographic algorithm on Fingerprints, Iris, face and palm simultaneously. In this paper we have explained the information about multimodal biometrics, DES algorithm, and role of DES in multimodal. We have discussed the implementation of DES algorithm by using MATLAB on parameters of captured images according to age and gender. Parameters such as key size, input size, time taken, simulation, memory requirement, CPU usage. Matching algorithm, time delay, FAR, FRR is also a major issue in multimodal biometrics.